Ácaros oribátidos (Acari: Oribatei) del Parque Nacional de la isla de Coiba, Panamá - Subías, L. (2004)
Taking part of the Program for The Inventory of Flora and Fauna of Coiba Island National Park (Panamá), a first list of oribatid mites (Acari: Oribatei) is presented. Materials studied come from several soil samplings, including humus and fallen leaves, done in Coiba Island in July 1998. 134 species were identified from a total amount of 1 053 individuals collected. Almost all the identified species are new records for Panamá as well as eigth species that represent first records for the Neotropical Region. A new name is given: Aeroppia mariehammerae n. nom. for Aeroppia sp. and a new combination is proposed: Protoribates antillensis (Mahunka, 1985) n. comb. (Xylobates).